Implementation of the Village Head Performance Law from the Perspective of Siyasah Tanfidhiyyah - Alfredo Jeremia; Imam Mahdi; Wery Gusmansyah (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the implementation of Law Number 3 of 2024 concerning the performance of the Village Head from the perspective of Siyasah Tanfidziyyah. This research employed a qualitative method using an empirical juridical approach. Data were collected through interviews, observations, and documentation. The findings indicate that the implementation of Law Number 3 of 2024 regarding the performance of the Head of Tanjung Seru Village has been carried out in terms of disseminating information to the community, submitting accountability reports, and providing protection and public services to the community. However, several shortcomings remain, including limited transparency of information, low levels of community participation, and the suboptimal implementation of the village head's protective role toward the community. From the perspective of Siyasah Tanfidziyyah, the Village Head's performance has not fully reflected the principles of amanah (trustworthiness), al-'adl (justice), and maslahah (public welfare). This is evident in the unequal dissemination of information, limited public involvement in governance processes, and the less-than-optimal execution of governmental duties aimed at promoting the interests and welfare of the community as a whole.